A composite fiber supercapacitor separator containing a cellulose lyotropic liquid gradient and a method of making the same
Patent Information
- Application Number
- CN202611183542.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]如果仅在隔膜整体中均匀加入纤维素亲液组分,可能会导致整体孔径过度下降、滤水困难或离子传输阻力增加;如果只在表面涂布亲液层,又可能出现涂层堵孔、脱落或表面亲液而内部浸润不足的问题
(1)本发明通过在未完全干燥状态下连续沉积相邻功能层,在相邻层之间形成可测量的纤维互穿过渡区,使亲液缺陷屏蔽层中的纤维素亲液组分进入承托层表层孔隙,形成连续亲液过渡,避免单纯表面涂布带来的堵孔和脱落问题,提高层间结合强度。
Smart Images

Figure CN123017748A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane technology for electrochemical energy storage devices, specifically to a cellulose-containing hydrophilic composite fiber supercapacitor membrane and its preparation method. Background Technology
[0002] The separator in a supercapacitor is positioned between the positive and negative electrodes. Its core function is to prevent direct contact between the electrodes to avoid internal short circuits, while simultaneously allowing the electrolyte to fully wet the capacitor and enabling rapid ion passage. As supercapacitors develop towards higher power, higher voltage, miniaturization, and automated winding, the separator is gradually evolving towards thinner, lower internal resistance, higher withstand voltage, and higher process stability.
[0003] Low-cost polyester, polypropylene, polyethylene, and their bicomponent thermally bonded fibers are suitable for wet nonwoven or papermaking processes, providing good mechanical skeleton and slitting strength. However, their surface hydrophilicity is generally not as good as that of cellulose fibers. When the proportion of synthetic fibers in the membrane is high, problems such as insufficient local wetting, slow local electrolyte spreading, insufficient liquid retention capacity, and high ESR are prone to occur.
[0004] Cellulose fibers and their micro / nano-sized components possess excellent electrolyte wettability, low raw material costs, and superior adaptability to wet molding processes, making them suitable for use as hydrophilic components, microporous interstitial components, and interfacial bonding modifiers in membranes. In particular, nanocellulose or in-situ micro / nano-sized cellulose, with its high aspect ratio, large specific surface area, and abundant hydroxyl structures, can form a dense micro / nano-sized interstitial network within composite fiber networks. This improves the hydrophilicity of the synthetic fiber surface and the uniformity of electrolyte spreading, and fills in localized macropores formed between fiber overlaps.
[0005] If the cellulose hydrophilic component is uniformly added to the entire membrane, it may lead to an excessive decrease in overall pore size, difficulty in water filtration, or increased resistance to ion transport. If the hydrophilic layer is only coated on the surface, problems such as coating blockage, peeling, or insufficient internal wetting may occur. Therefore, a composite fiber supercapacitor membrane with a controllable cellulose hydrophilic gradient in the thickness direction is needed, which can form a hydrophilic and microporous interstitial enrichment zone in the defect shielding layer while maintaining the mechanical skeleton of the support layer and the liquid conduction channel. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a composite fiber supercapacitor diaphragm containing a cellulose hydrophilic gradient and its preparation method, so that by using a low proportion of cellulose hydrophilic component in the support layer, a high proportion of cellulose hydrophilic component in the hydrophilic defect shielding layer, and a micro-nano cellulose enrichment structure, the wetting speed, liquid retention capacity, and pore size uniformity can be improved, while reducing the probability of the formation of through-holes and weak insulation points.
[0007] To solve the above-mentioned technical problems, one object of the present invention is to provide a composite fiber supercapacitor separator containing a cellulose hydrophilic gradient, wherein the separator is a multi-level fiber network composite structure, and the number of layers in the multi-level fiber network composite structure is an odd number of layers, such as three, five, seven, or nine or more. When the diaphragm has a three-layer structure, it includes, in sequence along the thickness direction, a support layer, a hydrophilic defect shielding layer, and a support layer; When the diaphragm is a multi-level odd-numbered structure with five, seven, nine or more layers, the diaphragm includes at least two of the hydrophilic defect shielding layers, and an intermediate liquid-conducting buffer layer is provided between any two adjacent hydrophilic defect shielding layers. The supporting layer independently comprises non-conductive artificial chopped fibers, thermally bonded fibers, and a cellulose hydrophilic component; the hydrophilic defect shielding layer independently comprises micro-filled interstitial fibers and a cellulose hydrophilic component; and the intermediate fluid-conducting buffer layer independently comprises non-conductive artificial chopped fibers, micro-filled interstitial fibers, and a cellulose hydrophilic component. The cellulose hydrophilic gradient is an asymmetric hydrophilic gradient. The hydrophilic defect shielding layer has a cellulose hydrophilic component content of at least 20% higher than that of the support layer. Furthermore, the mass proportion of the cellulose hydrophilic component in the first support layer, which is closer to the side with a higher risk of electrode burrs, is higher than that in the second support layer. This forms an asymmetric cellulose hydrophilic gradient distributed along the thickness direction. Alternatively, the shielding layer of the diaphragm may have a symmetrical structure, and the shielding layer of the diaphragm may be enriched with cellulose hydrophilic components relative to the support layer, with the hydrophilic defect shielding layer having at least 30% higher cellulose hydrophilic components than the support layer; The defect shielding layer forms a fiber interpenetrating transition region with a thickness of 0.2 to 8.0 μm between itself and the adjacent first support layer and second support layer. The total thickness of the diaphragm is 5–40 μm, and the total amount is 3–20 g / m³. 2 The single-layer quantitative amounts of the first and second support layers are 1.0–4.2 g / m³, respectively. 2 The quantitative composition of the defect shielding layer is 0.3–3.2 g / m³. 2 The quantitative amount of the intermediate liquid-conducting buffer layer is 1.3–5.0 g / m³. 2 Each of the aforementioned defect shielding layers accounts for 7wt% to 30wt% of the total mass of the diaphragm, and all of the aforementioned defect shielding layers account for 10wt% to 45wt% of the total mass of the diaphragm. The area index of through-hole defects in the diaphragm is no greater than 0.12%; In a 100-point Hipot test, the proportion of test points with a breakdown voltage below 500V is no more than 1%. The orientation angle between the main fibers of adjacent layers in the first support layer, alternating layer, and second support layer is 5° to 45°.
[0008] In this invention, the support layer is mainly composed of non-conductive chopped synthetic fibers and thermally bonded fibers, and contains a low proportion of cellulose hydrophilic components. Located on the outermost side of the separator, it primarily serves as a skeletal support and overall shaping element, while also ensuring electrolyte wetting. The non-conductive chopped synthetic fibers, as the basic skeletal material of the separator, provide mechanical strength and structural support, ensuring the separator maintains morphological stability during battery assembly and charge-discharge cycles. The thermally bonded fibers, as the binder component, melt or soften during subsequent drying or heat treatment, bonding the non-conductive chopped synthetic fibers together, thereby giving the separator sufficient physical strength and integrity. The cellulose hydrophilic component, as a hydrophilic / electrolyte-friendly modifier, imparts good electrolyte wettability and electrolyte retention to the support layer, reducing the interfacial impedance between the separator and the electrolyte, which is beneficial for rapid ion transport.
[0009] The defect shielding layer, enriched with fine interstitial fibers, is located between the two support layers and is the core functional layer of the diaphragm, primarily serving to safely intercept and construct gradient channels. The core function of these fine interstitial fibers is "interstitial filling" and "shielding." Due to their tiny size, they significantly reduce the average flow pore size of this layer (0.05–0.30 μm), effectively intercepting minute particles or dendrites in the electrode material and preventing internal short circuits.
[0010] Furthermore, the asymmetric hydrophilic gradient refers to the fact that the content of cellulose hydrophilic component in the support layer on the side with a higher risk of electrode burrs is higher than that in the support layer on the other side; the cellulose hydrophilic component in the support layer accounts for 2wt% to 35wt% of the dry weight of the corresponding support layer, and the cellulose hydrophilic component in the hydrophilic defect shielding layer accounts for 15wt% to 75wt% of the dry weight of the corresponding hydrophilic defect shielding layer.
[0011] The cellulose hydrophilic component content or micro-nanoization degree in the defect shielding layer is higher than that in the adjacent support layer, thereby forming a gradient in cellulose content, micro-nano structure, and hydrophilic properties along the thickness direction. This allows the membrane to possess rapid wetting, high liquid absorption and retention rates, and a more uniform microporous structure. Furthermore, by precisely adjusting the cellulose hydrophilic component content, micro-nanoization degree, beating degree, or fine fiber ratio in the slurry of each functional layer, a centrally enriched cellulose hydrophilic gradient is successfully constructed along the membrane thickness direction. This results in superior hydrophilic properties in the central region of the membrane, which is beneficial for rapid electrolyte absorption and retention, while also ensuring the overall mechanical strength and dimensional stability of the membrane.
[0012] Furthermore, the cellulose hydrophilic component of the support layer accounts for 2wt% to 35wt% of the dry weight of the corresponding support layer, and the cellulose hydrophilic component in the hydrophilic defect shielding layer accounts for 15wt% to 75wt% of the dry weight of the corresponding hydrophilic defect shielding layer.
[0013] Furthermore, the outer surface of the support layer contains a cellulose hydrophilic component, so that the initial contact angle of the electrolyte on both sides of the diaphragm is no greater than 45°, preferably no greater than 35°; the initial contact angle of the electrolyte in the hydrophilic defect shielding layer is smaller than the initial contact angle of the electrolyte in the support layer.
[0014] This invention makes the contact angle of the hydrophilic defect shielding layer smaller (i.e., more hydrophilic), allowing the electrolyte to be preferentially and rapidly absorbed and spread by the shielding layer. This is equivalent to forming a dense "liquid film buffer layer" in the area where electrode burrs may come into contact, using the surface tension of the liquid to offset some of the mechanical stress, thereby effectively shielding the membrane from the risk of burrs piercing it. The smaller contact angle means that the layer has excellent capillary effect. During the membrane injection stage, the shielding layer can instantly capture the electrolyte and release it slowly and evenly to the supporting layers on both sides as a "reservoir". This design avoids "dry spots" or uneven wetting of the electrolyte inside the membrane, ensuring that the ion transport channels are unobstructed during the charging and discharging of the supercapacitor, and significantly reducing the equivalent series resistance (ESR). By using the difference in contact angle, an osmotic pressure difference of the electrolyte in the thickness direction is artificially created. This gradient wetting mechanism can guide the electrolyte to fill the pores along a preset path, and together with the "misaligned pore structure", it further improves the membrane's liquid retention capacity.
[0015] Furthermore, the cellulose hydrophilic component includes plant pulp and its fine components and micro / nano cellulose, wherein the micro / nano cellulose is selected from one or more of in-situ micro / nano cellulose, microfibrillated cellulose, cellulose nanofibers, cellulose nanocrystals, and bacterial cellulose; and the plant pulp and its fine components are selected from one or more of bleached hardwood pulp, bleached bamboo pulp, cellulose pulp, softwood pulp, cotton pulp, and hemp pulp. The non-conductive man-made chopped fibers are selected from one or more of polyester chopped fibers, polypropylene chopped fibers, polyethylene chopped fibers, polyamide chopped fibers, and polylactic acid chopped fibers. The microfibers are selected from one or more of the following: microfibers, split polyester fibers, polyolefin microfibers, synthetic pulp, and papermaking fine fibers. The thermal bonding fiber is selected from one or more of low melting point polyester fiber, copolyester / polyester core-sheath fiber, polyethylene / polyester core-sheath fiber and polyethylene / polypropylene core-sheath fiber; Wherein, the softening point or melting point of the thermally bonded fiber is lower than that of the non-conductive artificial chopped fiber; the thermally bonded fiber forms a discontinuous dot-like bonded structure after being heat-pressed or heat-set, the area coverage of the discontinuous dot-like bonded structure in the plane direction of the diaphragm is 1% to 35%, and no continuous hot melt film layer is formed inside the diaphragm.
[0016] Furthermore, the average length of the non-conductive man-made chopped fibers and thermally bonded fibers is 1.0–6.0 mm, and the average linear density is 0.1–2.5 dtex; the average length of the micro-filler fibers is 0.05–1.5 mm, and the fiber width or diameter is 0.5–5.0 μm; the average length of the fine components of the plant pulp is 0.05–0.25 mm, the fiber width is 10–30 μm, and the mass ratio of the fine components is 60 wt%–95 wt%; the average length of the micro-nano cellulose is 0.5–20 μm, and the fiber diameter is 10–500 nm.
[0017] Furthermore, the fiber composition of each layer, by weight, is as follows: In the support layer, there are 35 to 92 parts of non-conductive artificial short-cut fibers, 5 to 45 parts of thermal bonding fibers, 2 to 35 parts of cellulose hydrophilic components, and 0 to 25 parts of micro-fine interstitial fibers; In the hydrophilic defect shielding layer, the micro-filling fiber is 20-80 parts, the cellulose hydrophilic component is 15-75 parts, and the thermal bonding fiber or synthetic pulp is 0-35 parts; In the intermediate fluid-conducting buffer layer, there are 20 to 70 parts of non-conductive artificial short-cut fibers, 10 to 50 parts of fine interstitial fibers, 5 to 50 parts of cellulose hydrophilic components, and 0 to 30 parts of thermal bonding fibers.
[0018] Furthermore, the average flow rate pore size of the hydrophilic defect shielding layer is 0.03–0.30 μm; the average flow rate pore size of each of the supporting layers is independently 0.20–2.20 μm; and the average flow rate pore size of the intermediate liquid-conducting buffer layer is 0.15–1.20 μm. Furthermore, the ratio of the average flow rate pore size of the supporting layer to the average flow rate pore size of the hydrophilic defect shielding layer is 1.8 to 12.0.
[0019] Furthermore, the diaphragm satisfies at least one of the following correspondences between thickness and quantity: when the total thickness of the diaphragm is 5–12 μm, the total quantity is 3–8 g / m³. 2 When the total thickness of the diaphragm is 12–25 μm, the total amount is 6–15 g / m³. 2 When the total thickness of the diaphragm is 25–40 μm, the total amount is 10–20 g / m³. 2 .
[0020] Furthermore, the liquid absorption rate of the diaphragm is 200%–650%, the liquid retention rate is 160%–320%, and the electrolyte wetting time does not exceed 10s; the area index of the through-hole defect of the diaphragm is not greater than 0.08%; the interfacial peel strength of the interpenetrating fiber transition zone is not less than 0.02N / 15mm, preferably not less than 0.05N / 15mm.
[0021] The second objective of this invention is to provide a method for preparing a composite fiber supercapacitor separator containing a cellulose hydrophilic gradient, comprising the following steps: (1) Prepare slurries for the support layer, the defect shielding layer and the intermediate liquid-conducting layer respectively; wherein, each of the support layers independently comprises non-conductive artificial short-cut fibers, thermal bonding fibers and cellulose hydrophilic components; each of the hydrophilic defect shielding layers independently comprises micro-filled interstitial fibers and cellulose hydrophilic components; each of the intermediate liquid-conducting buffer layers independently comprises non-conductive artificial short-cut fibers, micro-filled interstitial fibers and cellulose hydrophilic components; (2) Segmented vacuum dehydration: K1. The first support layer is wet-formed and dehydrated on a forming wire to prepare a first wet paper web with a solid content of 7wt% to 21wt%, in the state where the first wet paper web is not dried; K2. A layer of defect shielding slurry is deposited on the surface of the first wet paper web and partially dehydrated. The deposition interval between the two slurries is controlled to be no more than 180s, and a composite wet paper web with a solid content of 12wt% to 23wt% is prepared. K3. Before the composite wet paper web is completely dry, the second support layer pulp is deposited on the composite wet paper web and partially dehydrated to obtain a wet composite membrane with a solid content of 29wt% to 36wt%. The deposition interval between the two pulp layers is controlled to not exceed 180s. This allows the adjacent pulp layers to permeate each other in a wet state, forming a fiber interpenetration transition zone between the adjacent layers. Between steps K2 and K3, the following is also included: before the composite wet paper web is completely dried, a layer of intermediate liquid-conducting buffer slurry is deposited on the composite wet paper web and partially dehydrated to obtain a wet composite paper web with a solid content of 19wt% to 25wt%. Repeat step K2 to deposit a defect shielding layer slurry on the first wet paper web, or deposit multiple alternating layers of slurry and a defect shielding layer slurry in sequence, and partially dehydrate to obtain a composite wet paper web. The solid content of the composite wet paper web is greater than that of the wet composite paper web. The alternating layers include a hydrophilic defect shielding layer and an intermediate liquid-conducting buffer layer. (3) The wet slurry after lamination is pressed, dried or heat-set in sequence to obtain the composite fiber supercapacitor membrane containing cellulose hydrophilic gradient; The thickness of the interpenetrating fiber transition region is 0.2–8.0 μm, and the composite fiber membrane has a cellulose hydrophilic gradient in the thickness direction.
[0022] Furthermore, the interpenetrating transition zone of the fibers is formed by the infiltration of the micro-filling fibers and cellulose hydrophilic components in the defect shielding layer into the surface pores of the adjacent support layer, so that the pores of the adjacent layers form a gradient misaligned pore structure in the thickness direction.
[0023] Further, in step (1), the solid content of the supporting layer slurry is independently selected from 0.05wt% to 0.10wt%, the solid content of the defect shielding layer slurry is 0.015wt% to 0.050wt%, and the solid content of the intermediate liquid-conducting layer slurry is independently selected from 0.040wt% to 0.050wt%. In step (2), the time interval between the stacking deposition of two adjacent layers does not exceed 180s, so that the non-conductive artificial short-cut fibers, thermally bonded fibers, micro-filled fibers and cellulose hydrophilic components in the adjacent layers can interpenetrate in a wet state; In step (3), the heat setting treatment is heat pressing or heat setting, and its process parameters are: temperature 80~170℃, linear pressure 20~300kN / m, processing time 0.1~60s. By adjusting the running direction of the forming mesh, the pulp speed ratio, the spraying direction or the lip angle of the headbox, an orientation angle of 5°~45° is formed between the orientations of the main fibers of adjacent functional layers.
[0024] Furthermore, the solid content of the hydrophilic defect shielding layer slurry is lower than that of the supporting layer slurry, so as to control the deposition density of the micro-filling fibers and cellulose hydrophilic components in the hydrophilic defect shielding layer during the wet molding process.
[0025] Furthermore, the cellulose lyophilic group is subjected to pulping, decomposition, sieving, centrifugal classification, sedimentation classification, mechanical micro-nano treatment or white water recovery treatment to make it contain in-situ micro-nano cellulose, microfibrillated cellulose or cellulose nanofibrils, and then added to the corresponding slurry.
[0026] This step involves specific physical or chemical treatment of the cellulose hydrophilic component, resulting in the presence of in-situ micro / nano cellulose, microfibrillated cellulose (MFC), or cellulose nanofibers. These micro / nano-scale celluloses have a large specific surface area and abundant surface hydroxyl groups, which can significantly improve the hydrophilicity and electrolyte retention capacity of the membrane, thereby creating an excellent cellulose hydrophilic gradient in the membrane thickness direction to optimize its dispersibility in the slurry and its hydrophilic properties after film formation.
[0027] Furthermore, the continuous forming method is implemented using a cylinder paper machine, an inclined wire paper machine, a long wire paper machine, a multi-layer headbox, a vacuum filtration forming device, a cylinder-inclined wire composite forming device, or a combination thereof.
[0028] Furthermore, the spraying speed ratio or slurry net speed ratio of the functional layer slurry is 0.95 to 1.10.
[0029] Furthermore, by adjusting the running direction of the forming mesh, the speed ratio of the pulp mesh, the direction of the spraying, or the lip angle of the headbox, the orientation angle of the main fibers in adjacent layers can be made to be 5° to 45°.
[0030] The orientation angle difference of the main fibers in the different defect shielding layers is 20°, and the orientation angle difference between the main fibers in the first and second support layers and the adjacent shielding layers is 8° to 12°.
[0031] In this invention, the structure generated by each layer during wet composite has a synergistic effect: during the wet composite process, the micro-filling fibers and cellulose hydrophilic components in the defect shielding layer are "squeezed" into the surface pores of the adjacent support layer, forming a fiber interpenetrating transition zone with a thickness of 0.2 to 8.0 μm. This interpenetrating structure completely eliminates the "interlayer interface peeling" problem that easily occurs in traditional dry composite, making the three-layer structure integrated. At the same time, it makes the pore size of the membrane exhibit a smooth gradient change from the outside to the inside (gradient misaligned pore structure), which ensures that the large pores of the outer layer are conducive to rapid electrolyte wetting, and that the small pores of the inner layer can effectively shield defects, achieving a perfect balance between high ionic conductivity and high safety.
[0032] Furthermore, wet paper web moisture detection, online light transmission defect detection, and online thickness detection are set up on the continuous wet forming line. Based on the solid content of the first wet paper web and the light transmission defect signal, the pulp flow rate, vacuum degree, and pulp-to-wire speed ratio of the defect shielding layer are adjusted in real time to keep the thickness of the fiber interpenetration transition zone stable in the range of 1.5 to 3.5 μm.
[0033] The present invention also provides a supercapacitor, including a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the composite fiber gradient pore supercapacitor separator.
[0034] The diaphragm described in this invention can be used in electric double-layer supercapacitors, lithium-ion capacitors, organic electrolyte supercapacitors, aqueous supercapacitors, and other electrochemical energy storage devices that require ultra-thin, high-voltage, porous insulating diaphragms.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention continuously deposits adjacent functional layers in an incompletely dry state, forming a measurable fiber interpenetrating transition zone between adjacent layers, allowing the cellulose hydrophilic component in the hydrophilic defect shielding layer to enter the surface pores of the support layer, forming a continuous hydrophilic transition, avoiding the pore blockage and peeling problems caused by simple surface coating, and improving the interlayer bonding strength.
[0036] (2) Each layer of the present invention incorporates a cellulose hydrophilic component, which makes the membrane exhibit excellent hydrophilicity. During the electrolyte injection process, the electrolyte can quickly penetrate into the membrane, improving production efficiency. The hydrophilic component can "lock" in the electrolyte like a sponge, which can improve the electrolyte spreading uniformity of the low-cost artificial fiber system, reduce the area of insufficient local wetting, prevent the electrolyte from drying out during long-term circulation, and thus extend the service life of the supercapacitor.
[0037] (3) The present invention enriches the cellulose hydrophilic component in the shielding layer relative to the supporting layer, so that the supporting layer maintains the mechanical skeleton and liquid guiding channel, and the hydrophilic defect shielding layer forms a hydrophilic and microporous interstitial enrichment area, thereby taking into account wetting, liquid retention and low internal resistance; the enrichment of micro-nano cellulose in the hydrophilic defect shielding layer can utilize its high aspect ratio, large specific surface area and abundant hydroxyl structure to form a micro-nano interstitial network, improve pore size uniformity and reduce the probability of local through-hole formation.
[0038] (4) The present invention contains an appropriate amount of cellulose hydrophilic components in both support layers, so that both sides of the diaphragm have good initial electrolyte wetting ability, reducing local hydrophobic areas. By controlling the solid content of the first wet paper web, the deposition interval between adjacent layers and segmented vacuum dehydration, excessive mixing or complete separation between layers is avoided, so that the interface can both interpenetrate and maintain the pore size difference of each functional layer. Attached Figure Description
[0039] Figure 1 The three-station inclined wire mesh-vacuum continuous wet forming device consists of: 1-first support layer forming station, 2-defect shielding layer forming station, 3-second support layer forming station, 4-pressing zone, 5-drying zone, 6-hot pressing / heat setting zone, 7-cooling zone, 8-winding zone, 11-forming wire, 12-headbox and 13-segmented vacuum box; Figure 2 The five-station inclined wire mesh-vacuum continuous wet forming device consists of: 1-first support layer forming station, 2-first defect shielding layer forming station, 3-intermediate liquid guiding buffer layer forming station, 4-second defect shielding layer forming station, 5-second support layer forming station, 6-pressing zone, 7-drying zone, 8-hot pressing / heat setting zone, 9-cooling zone, 10-winding zone, 11-forming wire, 12-headbox, and 13-segmented vacuum box. Figure 3 The 10-minute aspiration height is the height of liquid in Example 1 and Comparative Example 1. Detailed Implementation
[0040] The following examples are provided to further illustrate the present invention, but are not intended to limit the scope of protection of the present invention. Without departing from the concept of the present invention, those skilled in the art can adjust the fiber type, fiber length, number of layers, layer thickness, basis weight, number of defect shielding layers, content of cellulose lyophilic components, molding method, and heat setting conditions. Unless otherwise specified, all raw materials used are commercially available industrial products that meet the following technical specifications, and the suppliers do not constitute a limitation on the scope of protection of the present invention.
[0041] In the embodiments of this invention, no specific manufacturer is limited for each raw material; the actual purchased grade only needs to meet the above specifications.
[0042] In the following examples, the raw materials, including white hardwood pulp, bleached bamboo pulp, plant fiber, clean fine fiber from white water recovery, cellulose pulp, softwood pulp, cotton pulp, hemp pulp and their graded fine components, all belong to plant pulp and their fine components, with fiber length of 0.05~0.30mm and fiber width of 10~30μm; In-situ micro-nano cellulose, microfibrillated cellulose, cellulose nanofibrils, cellulose nanocrystals, and bacterial cellulose all belong to micro-nano cellulose, with fiber lengths of 0.5~20μm and fiber diameters of 10~500nm; Microfibers, split polyester fibers, polyolefin microfibers, and synthetic pulp all belong to synthetic microfibers (microfibers that fill gaps between fibers), with fiber lengths of 0.05~1.50 mm and fiber widths or diameters of 0.5~5.0 μm; Cellulose lyophilic components include plant pulp and its fine components, and micro-nano cellulose.
[0043] The skeleton fibers include non-conductive man-made chopped fibers and thermal bonding fibers. The non-conductive man-made chopped fibers include polyester chopped fibers, polypropylene chopped fibers, polyethylene chopped fibers, polyamide chopped fibers and polylactic acid chopped fibers. The thermal bonding fibers include low-melting-point polyester thermal bonding fibers and polyethylene / polypropylene sheath-core thermal bonding fibers. The length of the skeleton fibers is 1.5~3.0mm.
[0044] Plant pulp and its fine components are first loosened for 10-20 minutes, and then pulped or graded according to the target fine fiber ratio; micro-nano cellulose is diluted with water dispersion and then dispersed at low shear for 5-15 minutes; micro-fine synthetic fibers or synthetic pulp are dispersed at 1500-2500 r / min for 10-20 minutes; split polyester fibers are hydraulically loosened or pulped in an aqueous medium at 20-60℃ for 10-30 minutes to fully split them before being mixed with other components.
[0045] Each slurry is prepared using deionized water with a conductivity not exceeding 10 μS / cm, and the pH is controlled at 6.5–7.5. Based on the dry weight of each fiber layer, 0.02 wt%–0.08 wt% of nonionic dispersant, 0.01 wt%–0.03 wt% of silicone-free defoamer, 0.01 wt%–0.05 wt% of nonionic wetting agent, and 0–0.02 wt% of low-ionic retention aid may be added, with the total amount of additives not exceeding 0.15 wt%.
[0046] Example 1
[0047] This embodiment provides an asymmetric anti-burr gradient pore membrane, comprising a first support layer, a defect shielding layer located between the first and second support layers, and a second support layer, all three layers being fiber network layers.
[0048] (1) Slurry preparation: The first support layer, by dry weight, comprises: 50 parts of chopped polyester fiber, 20 parts of low-melting-point polyester thermal bonding fiber, 25 parts of fine bleached hardwood pulp, and 5 parts of microfiber polyester fiber.
[0049] Defect shielding layer: by dry weight, it includes: 35 parts of microfiber polyester fiber, 15 parts of microfibrillated cellulose, 30 parts of fine natural plant fiber components, and 20 parts of low-melting-point polyester thermal bonding fiber.
[0050] Second support layer: 65 parts polyester chopped fiber, 20 parts copolyester / polyester core-sheath thermal bonding fiber, 10 parts bleached hardwood pulp fines, and 5 parts micro polyester fiber.
[0051] The first support layer is located on the side with a higher risk of electrode burrs. The cellulose hydrophilic components in the first support layer, the hydrophilic defect shielding layer, and the second support layer are 25 parts, 45 parts, and 10 parts, respectively. The hydrophilic defect shielding layer has a higher concentration of cellulose hydrophilic components than the two support layers by 20 and 35 percentage points, respectively, and the first support layer has a higher concentration of cellulose hydrophilic components than the second support layer by 15 percentage points.
[0052] The diaphragm exhibits significant asymmetry. The average flow pore size of the first support layer corresponding to a single-layer reference sample is 0.62 μm, the second support layer is 0.98 μm, and the defect shielding layer is 0.19 μm. In the burr resistance test, attaching the side with a higher burr risk (such as the positive electrode sheet) to the first side effectively prevents dendrite or burr penetration, significantly reducing the short-circuit rate. The average flow pore size of the support layer increases with the increase of the proportion of coarse skeleton fibers and decreases with the increase of the proportion of fine cellulose components and micro-filler fibers.
[0053] The technical specifications of the raw materials used in this embodiment are as follows: The polyester staple fiber is mainly composed of polyethylene terephthalate, with a polyester mass fraction of not less than 98.5 wt%, a fiber length of 1.5–3.0 mm, a linear density of 0.3–1.5 dtex, a breaking strength of not less than 3.0 cN / dtex, a melting point of 250–260℃, a moisture content of not more than 0.5 wt%, and an ash content of not more than 0.10 wt%. Low-melting-point polyester thermal bonding fiber is a copolyester / polyester core-sheath type or parallel type fiber with a fiber length of 1.5-3.0 mm and a linear density of 0.8-2.2 dtex. When it is a copolyester / polyester core-sheath type fiber, the sheath softening temperature is 105-125℃ and the core melting point is 250-260℃. When hot pressing and calendering is performed at 115-135℃, the sheath softens or partially melts, while the core maintains its skeletal shape. When it is a copolyester / polyester parallel type fiber, the softening temperature is 90-115℃ and the melting temperature is 105-135℃. Bleached hardwood pulp: The α-cellulose content of the masterbatch is not less than 85%, and the ash content is not more than 0.20%; the mass ratio of fine fibers with a length not greater than 0.20 mm after grading is 60% to 95%, the length-weighted average fiber length is 0.05 to 0.20 mm, and the freeness according to Canadian standards is 20 to 150 mL; The microfibers have an average diameter of 0.5–3.0 μm, a length of 0.10–1.50 mm, an aspect ratio of not less than 50, a melting point of 250–260 °C, and a moisture content of not more than 0.5 wt%. The microfibrillated cellulose has a diameter of 20–300 nm, a length of 1–20 μm, a solid content of 1 wt%–3 wt% when supplied as an aqueous dispersion or prepared, an ash content of no more than 0.50 wt%, and an electrical conductivity of no more than 100 μS / cm. The proportion of fine fibers with a length not exceeding 0.20 mm in the natural plant fiber fine component is 60%–95 wt%, the length-weighted average fiber length is 0.05–0.25 mm, the average fiber width is 5–30 μm, the freeness according to Canadian standards is 20–180 mL, the ash content is not higher than 0.30 wt%, and the conductivity of the aqueous dispersion is not higher than 100 μS / cm.
[0054] The copolyester / polyester sheath-core thermally bonded fiber has a fiber length of 1.5–3.0 mm and a linear density of 0.8–2.2 dtex; the sheath / core mass ratio is 30:70–50:50, preferably 40:60; the copolyester sheath has a softening temperature of 90–115°C and a melting temperature of 105–130°C, and the core is PET with a melting point of 250–260°C. During hot pressing at 115–135°C, the sheath softens or partially melts, while the core maintains its skeletal structure.
[0055] In the embodiments, no specific manufacturer is limited for each raw material; the actual purchased grade only needs to meet the above specifications.
[0056] All pulps are prepared using deionized water with a conductivity not exceeding 10 μS / cm. The pH of the pulp is controlled at 6.5–7.5, and the conductivity after pulp preparation is not higher than 100 μS / cm. Based on the dry weight of each fiber layer, the following additives may be added: 0.02%–0.08 wt% nonionic dispersant, 0.01%–0.03 wt% silicone-free defoamer, 0.01%–0.05 wt% nonionic wetting agent, and 0–0.02 wt% low-ionic retention aid; the total amount of additives shall not exceed 0.15 wt%. After papermaking, deionized water is used for spray replacement until the conductivity of the final filtrate is not higher than 50 μS / cm, in order to reduce the residual soluble ions.
[0057] Plant pulp and its fine components are first loosened for 10-20 minutes, and then pulped or graded according to the target fine fiber ratio; micro-nano cellulose is diluted with water dispersion and then dispersed at low shear for 5-15 minutes; micro-fine polyester fibers, polyolefin micro-fibers or synthetic pulp are dispersed at 1500-2500 r / min for 10-20 minutes; split polyester fibers are first hydraulically loosened or pulped in an aqueous medium at 20-60℃ for 10-30 minutes to achieve a splitting rate of more than 70%, and then mixed with skeleton fibers to form pulp.
[0058] The slurry for the first and second support layers is prepared with a solid content of 0.05 to 0.10 wt%, preferably 0.080 wt%, and the slurry for the defect shielding layer is prepared with a solid content of 0.015 to 0.050 wt%, preferably 0.030 wt%.
[0059] (2) In this embodiment, the above-mentioned diaphragm is prepared by a wet-state lamination composite process. The specific steps are as follows: Wet stratified sedimentary deposits: A three-station inclined mesh-vacuum continuous wet forming device with an effective width of 300mm is used, such as... Figure 1 As shown, the three-station inclined wire mesh-vacuum continuous wet forming device includes a first support layer forming station 1, a defect shielding layer forming station 2, a second support layer forming station 3, a pressing zone 4, a drying zone 5, a hot pressing / heat setting zone 6, a cooling zone 7, and a winding zone 8. Each station has an independent forming wire mesh 11, a headbox 12, and a segmented vacuum box 13. The forming wire mesh speed is 3.0 m / min.
[0060] Each layer of pulp is fed to the forming wire at a preset flow rate and undergoes preliminary gravity filtration for 2–5 seconds. Simultaneously, it is vacuum dehydrated in a segmented vacuum chamber to the preset solids content. If the online microwave moisture meter reading is stable within ±1.5 percentage points of the preset solids content target value and the change rate of drainage per unit area in the vacuum chamber is less than 5%, the dehydration endpoint is reached. Following the preset deposition sequence, the next layer of pulp is deposited sequentially while the previous wet paper web is not yet dry. The deposition interval between adjacent layers is 5–30 seconds. The preset deposition sequence is the first support layer, the defect shielding layer, and the second support layer. The preset flow rate for the three target pulp layers corresponding to the preset deposition sequence is calculated based on the web width, wire speed, target layer basis weight, and pulp solids content. The calculation formula is Q = b × W × V / (1000 × C), where Q is the pulp flow rate (L / min) and b is the layer basis weight (g / m³). 2W represents the effective width in meters (m), V represents the wire speed in meters per minute (m / min), and C represents the solid content of the pulp by mass. The target pulp flow rates for the three layers are approximately 4.50, 9.00, and 4.50 L / min. The spraying directions of the three headboxes corresponding to the preset deposition sequence are preferably set to 0°, +8°, and 0° relative to the forward direction of the wet paper web, respectively, corresponding to pulp-to-wire speed ratios of 1.00, 0.96, and 1.02, ensuring that the orientation angle between the defect shielding layer and the main fiber of the supporting layer is approximately 8°.
[0061] After each layer of wet paper web is deposited, segmented vacuum chambers are used for dewatering. The relative vacuum levels are as follows: 5–10 kPa after the first support layer is deposited, 10–20 kPa after the defect shielding layer is deposited, and 25–40 kPa relative vacuum is used for final dewatering after the second support layer is deposited. The preset solids content of the wet paper web after each layer is controlled sequentially as 10% ± 2%, 15% ± 3%, and 32% ± 3%. The basis weight of each layer is maintained by adjusting the pulp flow rate, and the basis weight deviation of the web is controlled within ± 3%.
[0062] (3) Shaping and drying The three-layer composite wet film is first wet-pressed at a pressure of 0.15–0.40 MPa for 0.5–2.0 s, with the preferred wet pressing pressure set at 0.30 MPa for 2 s, followed by a main pressing at 0.80 MPa for 2 s. Subsequently, it is dried at low tension at 70–95 °C, preferably in a hot air zone at 90 °C for 60 s, with the wet paper web moisture content controlled at 10 wt%–15 wt%. It is then dried in a hot air zone at 120 °C for 40 s, reducing the moisture content to 4 wt%–8 wt% before entering the hot calendering process. The film is then treated for 15 seconds using a belt hot press at 115–135°C (preferably 120–128°C or 120°C), a linear pressure of 40–100 kN / m (preferably 60–80 kN / m or 80 kN / m), and a linear speed of 1–5 m / min (preferably 2 m / min). This softens the low-melting-point polyester fiber sheath, forming discontinuous point adhesion instead of a continuous melt film. When the effective roll gap contact width is 3–8 mm, 1–3 calendering passes can be performed. Immediately after hot pressing, the film is cooled between cooling rollers at 20–40°C with a linear pressure of 10–30 kN / m (preferably 30 kN / m) until the film temperature is below 45°C. Finally, it is wound up with a low tension of 0.5–2.5 N / m to prevent re-adhesion and heat shrinkage.
[0063] In this embodiment, the target quantification for each layer is 4.0, 3.0, and 4.0 g / m³, respectively. 2 The final membrane thickness was approximately 24.5 μm, and the total quantitative amount was approximately 11.0 g / m³. 2 .
[0064] Example 2
[0065] This embodiment provides an asymmetric anti-burr five-layer composite fiber supercapacitor diaphragm, wherein the diaphragm structure is a first support layer / a first defect shielding layer / an intermediate fluid-conducting buffer layer / a second defect shielding layer / a second support layer.
[0066] The formulations of each functional layer are as follows: The first support layer consists of 55 parts of chopped polyester fiber, 20 parts of low-melting-point polyester thermal bonding fiber, 15 parts of fine bleached hardwood pulp, and 10 parts of microfiber polyester fiber. The first defect shielding layer consists of 40 parts of fine polyester fiber, 45 parts of microfibrillated cellulose, 10 parts of synthetic pulp, and 5 parts of thermal bonding fiber. The intermediate liquid-conducting buffer layer consists of 40 parts of chopped polyester fiber, 25 parts of fine polyester fiber, 25 parts of fine bleached hardwood pulp, and 10 parts of thermal bonding fiber. The second defect shielding layer consists of 50 parts of micro-fine polyester fiber, 20 parts of cellulose nanofibers, 20 parts of bleached hardwood pulp fine components, and 10 parts of thermal bonding fiber. The second support layer consists of 70 parts of chopped polyester fiber, 15 parts of low-melting-point polyester thermal bonding fiber, 10 parts of fine bleached hardwood pulp, and 5 parts of microfiber polyester fiber.
[0067] The cellulose hydrophilic components in the first support layer, the first defect shielding layer, the intermediate fluid-conducting buffer layer, the second defect shielding layer, and the second support layer are 15, 45, 25, 40, and 10 parts, respectively.
[0068] The technical specifications of the raw materials used in this embodiment are as follows: Cellulose nanofibers have a diameter of 20–300 nm, a length of 1–20 μm, a solid content of 1 wt%–3 wt% when supplied or prepared as an aqueous dispersion, an ash content of no more than 0.50 wt%, and an electrical conductivity of no more than 100 μS / cm; the fibrillated fibers of synthetic pulp have a width of 0.2–5.0 μm, a length of 0.05–1.0 mm, and an aspect ratio of no less than 20.
[0069] The heat-bonded fibers include copolyester / polyester core-sheath type or parallel type fibers, with a fiber length of 1.5 to 3.0 mm and a linear density of 0.8 to 2.2 dtex. When it is a copolyester / polyester core-sheath type fiber, the sheath softening temperature is 105 to 125°C and the core melting point is 250 to 260°C. During hot pressing at 115 to 135°C, the sheath softens or partially melts, while the core maintains its skeletal shape. When it is a copolyester / polyester parallel type fiber, the softening temperature is 90 to 115°C and the melting temperature is 105 to 135°C.
[0070] The pulp is prepared using deionized water with a conductivity not exceeding 10 μS / cm, and the pH is controlled at 6.5–7.5. The conductivity after pulp preparation should not exceed 100 μS / cm. Based on the dry weight of each fiber layer, the following additives may be added: 0.02%–0.08 wt% nonionic dispersant, 0.01%–0.03 wt% silicone-free defoamer, 0.01%–0.05 wt% nonionic wetting agent, and 0–0.02 wt% low-ionic retention aid; the total amount of additives should not exceed 0.15 wt%. After papermaking, deionized water is used for spray replacement until the conductivity of the final filtrate is not higher than 50 μS / cm, in order to reduce the residual soluble ions.
[0071] In this embodiment, the above-mentioned separator is prepared using a wet multilayer co-network molding process. The specific steps are as follows: (1) Pulp preparation and quantitative distribution: Plant pulp and its fine components are first loosened for 10-20 min, and pulped or graded according to the target fine fiber ratio; micro-nano cellulose is diluted with water dispersion and then dispersed at low shear for 5-15 min; micro-fine polyester fiber, polyolefin micro-fiber or synthetic pulp is dispersed at 1500-2500 r / min for 10-20 min respectively; and then mixed with skeleton fiber to prepare pulp.
[0072] Among them, the minimum solid content of the shielding layer is conducive to the uniform dispersion of micro-nano fibers, and the solid content of the buffer layer is between that of the support layer and the shielding layer. The preferred solid contents of the slurry in the support layer, shielding layer and buffer layer are 0.060wt%, 0.020wt% and 0.040wt%, respectively, and the target quantitative amounts of the first support layer / first defect shielding layer / intermediate liquid-conducting buffer layer / second defect shielding layer / second support layer are 3.8, 2.2, 4.0, 2.2 and 2.8 g / m³, respectively. 2 Calculate the total dry matter content of each slurry layer and adjust the coating amount of each slurry layer based on the target effective coating area.
[0073] (2) Wet lamination equipment and deposition: A five-station inclined mesh-vacuum continuous wet forming device with an effective width of 300mm is used, such as Figure 2 As shown, the five-station inclined wire mesh-vacuum continuous wet forming device includes a first support layer forming station 1, a first defect shielding layer forming station 2, an intermediate liquid guiding buffer layer forming station 3, a second defect shielding layer forming station 4, a second support layer forming station 5, a pressing zone 6, a drying zone 7, a hot pressing / heat setting zone 8, a cooling zone 9, and a winding zone 10. Each station has an independent forming wire 11, a headbox 12, and a segmented vacuum box 13. The forming wire speed is 2.5 m / min.
[0074] Each layer of pulp is fed to the forming wire at a preset flow rate and then undergoes preliminary gravity filtration for 2-5 seconds. Simultaneously, it is vacuum dehydrated in a segmented vacuum chamber to the preset solid content. If the online microwave moisture meter reading is stable within ±1.5 percentage points of the preset solid content target value and the change rate of drainage per unit area of the vacuum chamber is less than 5%, then the dehydration endpoint is reached. Following the preset deposition sequence, the next layer of pulp is deposited in sequence while the previous wet paper web is not dry. The deposition interval between adjacent layers is 40 seconds. The preset deposition sequence is as follows: first support layer, first defect shielding layer, intermediate liquid guiding buffer layer, second defect shielding layer, and second support layer.
[0075] The preset flow rate of the five target slurries corresponding to the preset deposition sequence is calculated based on the web width, net velocity, target layer quantity, and slurry solid content. The calculation formula is Q=b×W×V / (1000×C), where Q is the slurry flow rate in L / min and b is the layer quantity in g / m³. 2 W represents the effective width in meters (m), V represents the wire speed in meters per minute (m / min), and C represents the solid content of the pulp. The calculated preset flow rates for the five target pulp layers are approximately 4.75, 8.25, 7.50, 8.25, and 3.50 L / min, respectively. The preferred settings for the spraying direction of the five headboxes corresponding to the preset deposition sequence relative to the wet paper web's forward direction are 0°, +8°, 0°, -12°, and 0°, respectively. These correspond to wire speed ratios of 0.98, 1.03, 1.00, 0.97, and 1.02, resulting in an orientation angle of approximately 20° between the main fibers of the two defect shielding layers and an orientation difference of 8°–12° between the supporting layer and the adjacent shielding layer.
[0076] After each layer of wet paper web is deposited, segmented vacuum chambers are used for dewatering. The relative vacuum levels are as follows: 5–10 kPa after the first support layer, 18–25 kPa after the first and second defect shielding layers, 22–30 kPa after the intermediate liquid-conducting buffer layer, and 35–45 kPa for final dewatering after the second support layer. The preset solids content of the wet paper web after each layer is controlled sequentially as follows: 18% ± 2%, 20% ± 2%, 22% ± 2%, 24% ± 3%, and 32% ± 3%. The basis weight of each layer is maintained by adjusting the pulp flow rate, and the basis weight deviation of the web is controlled within ± 3%. The spraying directions of the five headboxes are 0°, +8°, 0°, -12°, and 0°, respectively.
[0077] (3) Pressing, drying and heat setting: The five-layer composite wet film is first wet pressed at a pressure of 0.15-0.40 MPa for 0.5-2.0 s, preferably with a wet pressing pressure of 0.30 MPa for 2 s, followed by a main pressing at 0.80 MPa for 2 s; then it is dried at low tension at 70-95℃, preferably in a hot air zone at 90℃ for 60 s, with the moisture content of the wet paper web controlled at 10wt%-15wt%, and then dried in a hot air zone at 120℃ for 40 s, so that the moisture content before entering the hot calendering is reduced to 4wt%-8wt%. Then, a belt hot calender is used to process the low-melting-point polyester fiber skin at 115-135℃ (preferably 120-128℃ or 122℃), 40-100kN / m linear pressure (preferably 100kN / m), and 1-5m / min linear speed (preferably 2m / min) for 20s. This softens the skin of the low-melting-point polyester fiber, forming discontinuous point adhesion instead of a continuous melt film. When the effective roller gap contact width is 3-8mm, 1-3 calendering passes can be used.
[0078] Immediately after hot pressing, the film is cooled between cooling rollers at 20-40°C with a linear pressure of 10-30 kN / m (preferably 30 kN / m) until the film temperature is below 45°C, and then wound up with low tension of 0.5-2.5 N / m to prevent re-adhesion and heat shrinkage.
[0079] The resulting membrane had a total thickness of approximately 24.5 μm and a total mass of approximately 15.0 g / m³. 2 The target quantifications for each layer were 3.8, 2.2, 4.0, 2.2, and 2.8 g / m³, respectively. 2 .
[0080] After hot pressing, the surface SEM or microscopic images are binarized to calculate the proportion of the projected area of the softened bonding points to the observed area. In this embodiment, the coverage rate of the bonding area is controlled at 8% to 15%, preferably about 10% to 12%, and continuous porous channels are maintained between adjacent bonding points.
[0081] In this embodiment, the total mass ratio of the micro-filling fibers and cellulose hydrophilic components in the first support layer is 20wt%, which is higher than the 10wt% in the second support layer. The first support layer is positioned closer to the side with a higher risk of electrode burrs.
[0082] Using a single-layer reference sample with the same formulation and measured by a capillary flow aperture meter, the average flow aperture of the first defect shielding layer was 0.16 μm, which was smaller than that of the second defect shielding layer (0.24 μm). The second defect shielding layer contained a total of 40 parts of finely bleached hardwood pulp components and cellulose nanofibers, used to improve liquid absorption and retention. This structure creates a stronger primary barrier on the burr side, while maintaining good electrolyte storage and ion transport capabilities on the other side.
[0083] Example 3
[0084] This embodiment provides a seven-layer, three-level defect-shielding hydrophilic gradient composite fiber supercapacitor diaphragm, wherein the diaphragm structure is a first support layer / a first defect shielding layer / a first intermediate liquid-conducting buffer layer / a second defect shielding layer / a second intermediate liquid-conducting buffer layer / a third defect shielding layer / a second support layer.
[0085] The raw material components and their dry weight fractions for each functional layer are as follows: The first support layer consists of 60 parts of chopped polyester fiber, 20 parts of low-melting-point polyester thermal bonding fiber, 15 parts of fine bleached hardwood pulp, and 5 parts of micro-fine polyester fiber. The first defect shielding layer consists of 35 parts of fine polyester fiber, 45 parts of microfibrillated cellulose, 10 parts of synthetic pulp, and 10 parts of thermal bonding fiber. The first intermediate liquid-conducting buffer layer consists of 30 parts of chopped polyester fiber, 30 parts of fine polyester fiber, 30 parts of fine bleached hardwood pulp, and 10 parts of thermal bonding fiber. The second defect shielding layer consists of 40 parts of micro-fine polyester fiber, 40 parts of cellulose nanofiber, 10 parts of synthetic pulp, and 10 parts of thermal bonding fiber. The second intermediate liquid-conducting buffer layer consists of 40 parts of chopped polyester fiber, 25 parts of fine polyester fiber, 25 parts of fine bleached hardwood pulp, and 10 parts of thermal bonding fiber. The third defect shielding layer consists of 55 parts of fine polyester fiber, 20 parts of microfibrillated cellulose, 15 parts of fine bleached hardwood pulp, and 10 parts of thermally bonded fiber.
[0086] The second support layer consists of 70 parts of chopped polyester fiber, 20 parts of low-melting-point polyester thermal bonding fiber, 5 parts of bleached hardwood pulp fines, and 5 parts of microfiber polyester fiber.
[0087] The cellulose hydrophilic components in the two support layers are 15 parts and 5 parts, respectively, and the cellulose hydrophilic components in the three hydrophilic defect shielding layers account for 45 wt%, 40 wt%, and 35 wt%, respectively, all of which are at least 20 percentage points higher than those in the support layers.
[0088] In this embodiment, the above-mentioned separator is prepared using a wet multilayer co-network molding process. The specific steps are as follows: (1) Pulp preparation and quantitative distribution: Plant pulp and its fine components are first loosened for 10-20 min, and pulped or graded according to the target fine fiber ratio; micro-nano cellulose is diluted with water dispersion and then dispersed at low shear for 5-15 min; micro-fine polyester fiber, polyolefin micro-fiber or synthetic pulp is dispersed at 1500-2500 r / min for 10-20 min respectively; and then mixed with skeleton fiber to prepare pulp.
[0089] The slurry for the first and second support layers is prepared with a solid content of 0.05–0.10 wt%, preferably 0.080 wt%. The slurry for the first, second, and third defect shielding layers is prepared with a solid content of 0.015–0.050 wt%, preferably 0.030 wt%. The slurry for the intermediate liquid-conducting buffer layer is prepared with a solid content of 0.050 wt%. The target quantities for the first support layer / first defect shielding layer / intermediate liquid-conducting buffer layer / second defect shielding layer / intermediate liquid-conducting buffer layer / third defect shielding layer / second support layer are 3.50, 2.60, 2.45, 2.30, 2.45, 2.40, and 3.50 g / m³, respectively. 2 Total amount 19.2g / m 2 Calculate the total dry matter content of each slurry layer and adjust the coating amount of each slurry layer based on the target effective coating area.
[0090] (2) Wet stacking equipment and deposition: A seven-station inclined screen-vacuum continuous wet forming device with an effective width of 300mm is used, wherein the forming screen speed is 2.0m / min.
[0091] Each layer of pulp is fed to the forming wire at a preset flow rate and then undergoes preliminary gravity filtration for 2-5 seconds. Simultaneously, it is vacuum dehydrated in a segmented vacuum chamber to the preset solid content. If the online microwave moisture meter reading is stable within ±1.5 percentage points of the preset solid content target value and the change rate of drainage per unit area of the vacuum chamber is less than 5%, then the dehydration endpoint is reached. Following the preset deposition sequence, the next layer of pulp is deposited in sequence while the previous wet paper web is not dry. The deposition interval between adjacent layers is 35 seconds. The preset deposition sequence is as follows: first support layer, first defect shielding layer, intermediate liquid-conducting buffer layer, second defect shielding layer, intermediate liquid-conducting buffer layer, third defect shielding layer, and second support layer.
[0092] The preset flow rate of the seven target slurries corresponding to the preset deposition sequence is calculated based on the web width, net velocity, target layer quantity, and slurry solid content. The calculation formula is Q=b×W×V / (1000×C), where Q is the slurry flow rate in L / min and b is the layer quantity in g / m³. 2 W represents the effective width in meters (m), V represents the head velocity in meters per minute (m / min), and C represents the solid content (mass fraction) of the slurry. The calculated preset flow rates for the seven target slurries are approximately 2.63, 5.20, 2.94, 4.60, 2.94, 4.80, and 2.63 L / min, respectively. The spraying directions of the seven headboxes are 0°, +8°, 0°, -12°, 0°, +8°, and 0°, respectively.
[0093] After each layer of wet paper web was deposited, segmented vacuum chambers were used for dewatering. The relative vacuum levels were as follows: 5–10 kPa after the first support layer was deposited; 18–25 kPa after the first and second defect shielding layers were deposited; 22–30 kPa after the intermediate liquid-conducting buffer layer was deposited; and 35–45 kPa relative vacuum was used for final dewatering after the second support layer was deposited. The final dewatered solids content was 34% ± 3%, and the basis weight of each layer was maintained by adjusting the pulp flow rate, with the basis weight deviation of the entire web controlled within ± 3%. The solids contents of the seven wet paper web layers were 18% ± 2%, 20% ± 2%, 22% ± 2%, 24% ± 2%, 26% ± 2%, 28% ± 3%, and 34% ± 3%, respectively.
[0094] (3) Pressing, drying and heat setting: The seven-layer composite wet film is first wet pressed at a pressure of 0.15-0.40 MPa for 0.5-2.0 s, preferably with a wet pressing pressure of 0.30 MPa for 2 s, followed by a main pressing at 0.80 MPa for 2 s; then it is dried at low tension at 70-95℃, preferably in a hot air zone at 90℃ for 60 s, with the moisture content of the wet paper web controlled at 10wt%-15wt%, and then dried in a hot air zone at 120℃ for 40 s, so that the moisture content before entering the hot calendering is reduced to 4wt%-8wt%. Then, a belt hot calender is used to process the low-melting-point polyester fiber skin at 115-135℃ (preferably 120-128℃ or 125℃), 40-120kN / m linear pressure (preferably 120kN / m), and 1-5m / min linear speed (preferably 2m / min) for 25s. This softens the skin of the low-melting-point polyester fiber, forming discontinuous point adhesion instead of a continuous melt film. When the effective roller gap contact width is 3-8mm, 1-3 calendering passes can be used.
[0095] Immediately after hot pressing, the film is cooled between cooling rollers at 20-40°C with a linear pressure of 10-30 kN / m (preferably 30 kN / m) until the film temperature is below 45°C, and then wound up with low tension of 0.5-2.5 N / m to prevent re-adhesion and heat shrinkage.
[0096] The resulting membrane had a total thickness of approximately 35.0 μm and a total mass of approximately 19.2 g / m³. 2 .
[0097] In this embodiment, the average flow rate pore sizes of the three defect shielding layers are approximately 0.16, 0.18, and 0.22 μm, respectively, and the average flow rate pore sizes of the two intermediate fluid-conducting buffer layers are approximately 0.55 and 0.65 μm, respectively. These pore sizes must be confirmed by actual measurements on a single-layer reference sample with the same formulation.
[0098] Example 4
[0099] This embodiment provides a centrally enriched cellulose hydrophilic gradient three-layer membrane and its preparation method.
[0100] The diaphragm includes, in sequence along its thickness direction, a first support layer, a hydrophilic defect shielding layer, and a second support layer.
[0101] The raw material components and their dry weight fractions for each functional layer are as follows: First and second support layers (with the same composition and proportions): 60 parts of chopped polyester fiber, 20 parts of low-melting-point polyester thermal bonding fiber, 15 parts of bleached hardwood pulp fines and 5 parts of micro-fine polyester fiber.
[0102] Liquid-sensitive defect shielding layer: 40 parts microfiber polyester fiber, 35 parts microfibrillated cellulose, 15 parts cellulose pulp, and 10 parts low-melting-point polyester thermal bonding fiber.
[0103] In this embodiment, the cellulose hydrophilic component (microfibrillated cellulose + plant pulp and its fine components) in the hydrophilic defect shielding layer accounts for 50% of the dry weight of the layer, which is about 35 percentage points higher than the cellulose hydrophilic component content (15%) in the support layer. The difference in the cellulose hydrophilic component between the hydrophilic defect shielding layer and the support layer in this embodiment is 20% greater than the difference in the cellulose hydrophilic component between the hydrophilic defect shielding layer and the support layer in Comparative Examples 5 and 6.
[0104] The preparation method used in this embodiment is the same as in Example 1, except that the target quantitative amounts for each layer in this embodiment are 3.65, 3.0, and 3.65 g / m³, respectively. 2 Total: 10.3 g / m 2 The preferred solid content of the slurry in the support layer, shielding layer, and support layer is 0.080, 0.030, and 0.080 wt%, respectively. Each layer was dehydrated using different relative vacuum degrees, with absolute vacuum values of 8, 18, and 35 kPa, respectively. The solid content of the wet paper web in the first support layer is controlled at 18 wt%, and the solid content of subsequent layers is controlled at 22% and 32% respectively after deposition. The fiber orientation angle between the hydrophilic defect shielding layer and the support layer is 8°.
[0105] The total thickness of the resulting membrane was 15.2 μm, and the total mass was 10.3 g / m³. 2 In the hydrophilic defect shielding layer, the fine components of bleached hardwood pulp and microfibrillated cellulose interweave to form a fiber-interpenetrating transition zone with a thickness of approximately 2.5 μm; the average flow pore sizes of each functional layer are specifically 0.70, 0.20, and 0.70 μm. The thickness of the fiber-interpenetrating transition zone is approximately 2.5 μm.
[0106] Example 5
[0107] This embodiment provides a nanocellulose-enriched hydrophilic shielding membrane and its preparation method.
[0108] The diaphragm includes, in sequence along its thickness direction, a first support layer, a hydrophilic defect shielding layer, and a second support layer.
[0109] The raw material components and their dry weight fractions for each functional layer are as follows: The first and second support layers, by dry weight, consist of: 55 parts of chopped polypropylene fibers, 30 parts of polyethylene / polypropylene core heat-bonding fibers, 10 parts of bleached bamboo pulp fines, and 5 parts of polyolefin microfibers; the defect shielding layer, by dry weight, consists of: 20 parts of cellulose nanofibers, 20 parts of microfibrillated cellulose, 40 parts of microfibrillated polyester fibers, and 20 parts of heat-bonding fibers.
[0110] In this embodiment, the cellulose hydrophilic component in the hydrophilic defect shielding layer accounts for 40 wt% of the dry weight of the layer, which is 30 percentage points higher than the cellulose hydrophilic component content in the support layer. The difference between the cellulose hydrophilic component in the hydrophilic defect shielding layer and the support layer in this embodiment is 15% greater than the difference between the cellulose hydrophilic component in the hydrophilic defect shielding layer and the support layer in Comparative Examples 5 and 6.
[0111] Thermo-bonded fiber has the following specific technical specifications: fiber length 1.5–3.0 mm, linear density 0.8–2.2 dtex; sheath / core mass ratio 30:70–50:50, preferably 40:60; polyethylene sheath softening temperature 80–105℃, melting temperature 105–135℃; polypropylene core melting point 155–170℃. During hot pressing at 110–130℃, the sheath softens or partially melts to form discontinuous point-like bonds, while the core maintains the fiber skeleton. After hot pressing, the point-bonded area coverage is controlled at 8%–15%, and a continuous hot-melt film layer is not formed.
[0112] The preparation method used in this embodiment is the same as in Example 1, except that the target quantitative amounts for each layer in this embodiment are 4.2, 3.2, and 4.2 g / m³, respectively. 2 Total: 11.6 g / m 2 The preferred solid content of the slurry in the supporting layer, shielding layer, and buffer layer is 0.080, 0.030, and 0.080 wt%, respectively. Each layer was dehydrated under relative vacuum at 8, 18, and 35 kPa in sequence; The solid content of the wet paper web in the first support layer is controlled at 20%, and the solid content of the subsequent layers after deposition is controlled at 23% and 34wt% respectively.
[0113] The total thickness of the resulting membrane was 18.0 μm, and the total mass was 12.0 g / m³. 2 In the hydrophilic defect shielding layer, cellulose nanofibers and microfibrillated cellulose intertwine to form a fiber interpenetrating transition region with a thickness of approximately 2.8 μm; the average flow pore sizes of each functional layer are specifically 0.65, 0.18, and 0.65 μm, and the thickness of the fiber interpenetrating transition region is approximately 2.8 μm.
[0114] Comparative Example 1: Uniformly compounded diaphragms without cellulose hydrophilic gradient.
[0115] The cellulose lyophilic component from Example 1 was evenly distributed into the three layers, so that the content of the cellulose lyophilic component in each of the three layers was 25 parts, and other process conditions were the same as in Example 1.
[0116] Comparative Example 2: Surface-liquefied diaphragm only.
[0117] According to Example 1, a composite fiber-based paper was first prepared, and then a cellulose hydrophilic dispersion was coated on one side of the paper and dried. It does not have a continuous hydrophilic gradient in the thickness direction and a wet fiber interpenetration transition zone.
[0118] Comparative Example 3: Three-layer membrane without nanocellulose.
[0119] The hydrophilic defect shielding layer uses only ordinary wood pulp fine components and microfiber polyester fibers, without micro-nano cellulose. The difference in cellulose hydrophilic component between the shielding layer and the support layer is 15 percentage points. Other process conditions are the same as in Example 1.
[0120] Comparative Example 4: Pure synthetic fiber diaphragm.
[0121] All three layers are made of polyester chopped fibers, polyolefin microfibers and thermal bonding fibers, and do not contain cellulose hydrophilic components. Other process conditions are the same as in Example 1.
[0122] Comparative Example 5: The difference in the lyophilic component of cellulose was 15 percentage points. A comparative example provides an ultrathin composite fiber gradient pore membrane with a total thickness of approximately 5.8 μm, comprising a first support layer, a defect shielding layer, and a second support layer that are sequentially stacked along the thickness direction and composited in a wet state. All three layers are fiber network layers, and the defect shielding layer is located between the first support layer and the second support layer.
[0123] The first supporting layer slurry, by dry weight, comprises: 65 parts of chopped polyester fibers, 20 parts of copolyester / polyester core-sheath thermal bonding fibers, 10 parts of fine bleached hardwood pulp components, and 5 parts of microfiber polyester fibers. The components are mixed in proportion to prepare a suspension with a solid content of 0.05%–0.10 wt%, preferably 0.08 wt%. The second support layer slurry has the same mix ratio and solid content as the first support layer slurry.
[0124] Defect shielding layer slurry: by dry weight, it includes: 45 parts of fine polyester fiber, 20 parts of split polyester fiber, 25 parts of in-situ micro-nano cellulose, and 10 parts of copolyester / polyester core-sheath thermal bonding fiber. The components are mixed in proportion to prepare a suspension with a solid content of 0.015 to 0.050 wt%, preferably 0.03 wt%.
[0125] In this embodiment, the above-mentioned separator was prepared using a wet-state lamination composite process, the process being the same as in Example 1; the total thickness of the resulting separator was approximately 5.8 μm, and the target quantitative amounts of the three layers were 1.2, 1.0, and 1.2 g / m³. 2 The total amount is approximately 3.4 g / m³. 2 .
[0126] Comparative Example 6: The difference in the lyophilic component of cellulose was 15 percentage points. This comparative example provides a polyolefin composite fiber gradient pore membrane with a total thickness of approximately 8.6 μm, comprising a first support layer, a defect shielding layer located between the first and second support layers, and a second support layer, all three layers being fiber network layers.
[0127] The first and second support layers, by dry weight, comprise: 50 parts chopped polypropylene fibers, 25 parts polyethylene / polypropylene core-sheath thermal bonding fibers, 15 parts bleached bamboo pulp fines, and 10 parts microfiber polyester fibers. The defect shielding layer, by dry weight, comprises: 30 parts polyolefin microfibers, 25 parts microfiber polyester fibers, 30 parts microfibrillated cellulose, and 15 parts synthetic pulp. The solids content of both the first and second support layer slurries is 0.08 wt%; the solids content of the defect shielding layer slurry is 0.030 wt%.
[0128] The target quantifications for the three layers were 1.8, 2.0, and 1.8 g / m³, respectively. 2 The total amount was 5.6 g / m³. 2 The cellulose lyophilic component was prepared using the same method as in Example 1, resulting in a membrane with a total thickness of approximately 8.6 μm and a total mass of approximately 5.6 g / m³. 2 .
[0129] The following performance tests were performed on Examples 1-5 and Comparative Examples 1-6. The specific test items and methods are as follows: (1) Thickness and basis weight: The thickness of the diaphragm is determined by the thickness test method applicable to electrical insulating paper or porous diaphragm; the basis weight is determined by the basis weight test method for paper and paperboard.
[0130] (2) Characterization of cellulose hydrophilic gradient: Using the same raw material composition, ratio, slurry solid content, single-layer quantitative method, and pressing, drying, and heat setting conditions as each functional layer, corresponding single-layer reference samples were prepared. The single-layer reference samples were cut into strips with a width of 15±0.5 mm and a length of 120-150 mm, and equilibrated in an environment of 23±2℃ and 50%±5% relative humidity for at least 24 h. The samples were suspended vertically, with the lower end immersed in the same electrolyte as that actually used in supercapacitors for 2.0±0.5 mm. Timing was started from the moment of contact with the electrolyte, and the vertical distance between the free liquid surface of the electrolyte and the continuous wetting front was measured after 10 min, which was recorded as the 10-min electrolyte capillary absorption height H10. Each group of tests had no less than 5 parallel samples. When the H10 of the hydrophilic defect shielding layer was higher than that of the adjacent support layer, and the H10 of the first support layer was higher than that of the second support layer, it was determined that an asymmetric cellulose hydrophilic gradient was formed.
[0131] (3) Soaking time, liquid absorption rate and liquid retention rate: The time required for the diaphragm to be completely soaked is recorded using the target electrolyte; the liquid absorption rate is calculated as (wetting mass - drying mass) / drying mass × 100%; the liquid retention rate is calculated as the ratio of the mass of electrolyte retained in the diaphragm after centrifugation or extrusion to the drying mass.
[0132] (4) Average flow orifice diameter: The average flow orifice diameter of the diaphragm as a whole or each functional layer of the reference sample with the same formulation was tested using a capillary flow orifice gauge.
[0133] (5) Thickness of the fiber interpenetration transition zone: The sample is embedded in resin and cross-section sectioned or ion beam prepared. The interface between adjacent layers is observed using a scanning electron microscope. The region where fibers from two adjacent layers coexist and are not separated in a straight line is defined as the fiber interpenetration transition zone. The thickness is measured at no less than 5 locations and the average value or range is taken.
[0134] (6) Through-hole area index: In no less than 5 cross-sectional fields of view, the through-hole extending continuously from one side surface to the other side surface is binarized and identified. The through-hole area index is the ratio of the projected area of the through-hole to the total area of the observation area.
[0135] (7) ESR and ionic conductivity: After the membrane is fully immersed in the target electrolyte, the ionic resistance of the membrane is measured by AC impedance method and the ionic conductivity is calculated; the equivalent series resistance is measured in a supercapacitor cell of specified specifications.
[0136] (8) Withstand voltage test: Place the diaphragm between two metal electrodes and perform a DC withstand voltage test, and record the breakdown voltage. Select 100 test points evenly for each sample and count the proportion of test points with a breakdown voltage below 500V.
[0137] (9) Process yield: During the slitting, winding or stacking process, count the number of broken strips, pinholes, thin spots, burrs, short circuits, pressure failures and appearance defects, and calculate the overall yield.
[0138] (10) Solid content test: Weigh the wet paper web sample, dry it to constant weight at the specified temperature, and then calculate the solid content.
[0139] (11) Interface peel strength test: Prepare the diaphragm sample according to the specified width, and test the peel or interlayer bonding strength of the adjacent layer interface, and record the peel force.
[0140] (12) Coverage of point bonding area: The microscopic image or scanning electron microscope image of the diaphragm surface is binarized, and the proportion of the projected area of the thermal bonding point to the observed area is statistically analyzed.
[0141] The lyophilic gradient structural parameters of cellulose are shown in Table 1. Table 1
[0142] The wet interpenetrating molding process parameters are shown in Table 2: Table 2 Wet interpenetrating molding process parameters
[0143] The ranking of liquid absorption height after 10 minutes and the overall liquid absorption and retention performance are shown in Table 3 and Figure 3 As shown: Table 3
[0144] The pore structure and electrochemical performance evaluation are shown in Table 4: Table 4
[0145] The through-hole defects and pressure resistance are shown in Table 5: Table 5
[0146] The overall yield rate of the manufacturing process is shown in Table 6: Table 6
[0147] The fiber interpenetrating interface structure is shown in Table 7: Table 7
[0148] In this invention, a lower proportion of cellulose hydrophilic components in the support layer improves the initial electrolyte spreading on both sides of the membrane while retaining the mechanical framework and liquid-conducting channels formed by the artificial short-cut fibers. A higher proportion of cellulose hydrophilic components and micro / nano-sized cellulose in the defect shielding layer forms a centrally enriched hydrophilic region, improving the membrane's internal liquid retention capacity and pore size uniformity.
[0149] Micro- and nano-sized cellulose possesses a high aspect ratio, a large specific surface area, and abundant hydroxyl structures, enabling it to form micro- and nano-interstitial networks together with micro-fine polyester fibers, split polyester fibers, and synthetic pulp. This network can improve electrolyte spreading and retention capacity, as well as fill localized large pores between fiber overlaps, reducing penetration defects and low pressure resistance points.
[0150] The interpenetrating transition zone formed by wet-state composite allows micro-nano cellulose and fine interstitial fibers in the hydrophilic defect shielding layer to enter the surface pores of the support layer, thereby forming a continuous hydrophilic transition and misaligned pore structure. Compared with surface-coated hydrophilic layers, the hydrophilic components of this invention are distributed inside the fiber network, making it less prone to coating peeling and local pore blockage problems.
[0151] This invention enables continuous deposition, controlled dehydration, and fiber interfacial migration in a partially dried state. While maintaining an appropriate solids content, the surface pores of the first wet paper web retain an open structure capable of receiving fine components from subsequent layers, while simultaneously possessing sufficient wet strength to prevent overall mixing.
[0152] After the second functional layer pulp is deposited, the low-vacuum leveling and dewatering stage allows the fine interstitial fibers and cellulose lyophilic components to enter the surface pores of the first functional layer, forming interpenetration and interlocking. Subsequently, medium-vacuum shaping and dewatering stabilizes the interlayer structure. If the initial vacuum is too high, the fine components will be instantly drawn through, leading to local defects; if the first wet paper web is over-dried, subsequent layers will have difficulty entering the surface pores and forming effective interpenetration.
[0153] The interpenetrating fiber transition zone transforms adjacent functional layers from a clear dry film bonding interface into an interlocking transition region. This transition region enhances interlayer bonding strength and causes pores to shift, branch, and block in the thickness direction, thereby reducing through-pores and low-pressure points.
[0154] Through low-tension transfer and thermal bonding point-like shaping, the interpenetrating interface is not easily damaged by stretching during drying, calendering, and winding. This method can serve as a common manufacturing platform for three-layer gradient pore membranes, ultrathin low-defect membranes, multi-level defect-shielding membranes, and cellulose hydrophilic gradient membranes.
[0155] The wet papermaking method for the composite fiber supercapacitor separator containing a cellulose hydrophilic gradient described in this invention can be implemented using existing cylinder paper machines, inclined wire paper machines, long wire paper machines, multilayer headboxes, vacuum filtration forming devices, or cylinder-inclined wire composite forming devices. The raw materials used are mainly non-conductive man-made chopped fibers, thermally bonded fibers, micro-filled fibers, and cellulose hydrophilic components, suitable for continuous industrial-scale production. The separator obtained by this invention can be used in electric double-layer supercapacitors, lithium-ion capacitors, organic electrolyte supercapacitors, aqueous supercapacitors, and other electrochemical energy storage devices requiring thin, high-voltage, porous insulating separators.
[0156] Although the above embodiments have described the present invention and its implementation in detail, it should be noted that for those skilled in the art, any changes, modifications, substitutions, combinations, simplifications, etc., made to the corresponding conditions without departing from the technical principles of the present invention should be considered as equivalent substitutions, and these improvements should also be considered within the scope of protection of the present invention.
Claims
1. A composite fiber supercapacitor separator containing a cellulose hydrophilic gradient, characterized in that, The diaphragm is a multi-level fiber network composite structure, and the number of layers in the multi-level fiber network composite structure is an odd number of layers, such as three, five, seven, or nine or more. When the diaphragm has a three-layer structure, it includes, in sequence along the thickness direction, a support layer, a hydrophilic defect shielding layer, and a support layer; When the diaphragm is a multi-level odd-numbered structure with five, seven, nine or more layers, the diaphragm includes at least two of the hydrophilic defect shielding layers, and an intermediate liquid-conducting buffer layer is provided between any two adjacent hydrophilic defect shielding layers. Each of the supporting layers independently comprises non-conductive artificial chopped fibers, thermally bonded fibers, and a cellulose hydrophilic component; each of the hydrophilic defect shielding layers independently comprises micro-filled interstitial fibers and a cellulose hydrophilic component; and each of the intermediate fluid-conducting buffer layers independently comprises non-conductive artificial chopped fibers, micro-filled interstitial fibers, and a cellulose hydrophilic component. The cellulose hydrophilic gradient is an asymmetric hydrophilic gradient. The hydrophilic defect shielding layer has a cellulose hydrophilic component content of at least 20% higher than that of the support layer. Furthermore, the mass proportion of the cellulose hydrophilic component in the first support layer, which is closer to the side with a higher risk of electrode burrs, is higher than that in the second support layer. This forms an asymmetric cellulose hydrophilic gradient distributed along the thickness direction. Alternatively, the shielding layer of the diaphragm may have a symmetrical structure, and the shielding layer of the diaphragm may be enriched with cellulose hydrophilic components relative to the support layer, with the hydrophilic defect shielding layer having at least 30% higher cellulose hydrophilic components than the support layer; The defect shielding layer forms a fiber interpenetrating transition region with a thickness of 0.2 to 8.0 μm between itself and the adjacent first support layer and second support layer. The total thickness of the diaphragm is 5–40 μm, and the total amount is 3–20 g / m³. 2 The single-layer quantitative amounts of the first and second support layers are 1.0–4.2 g / m³, respectively. 2 The quantitative composition of the defect shielding layer is 0.3–3.2 g / m³. 2 The quantitative amount of the intermediate liquid-conducting buffer layer is 1.3–5.0 g / m³. 2 Each of the aforementioned defect shielding layers accounts for 7wt% to 30wt% of the total mass of the diaphragm, and all of the aforementioned defect shielding layers account for 10wt% to 45wt% of the total mass of the diaphragm. The area index of through-hole defects in the diaphragm is no greater than 0.12%, and in a 100-point Hipot test, the proportion of test points with a breakdown voltage below 500V is no greater than 1%. The orientation angle between the main fibers of adjacent layers in the first support layer, alternating layer, and second support layer is 5° to 45°.
2. The composite fiber supercapacitor separator according to claim 1, characterized in that, The asymmetric hydrophilic gradient refers to the fact that the content of cellulose hydrophilic component in the support layer on the side with a higher risk of electrode burrs is higher than that in the support layer on the other side; the cellulose hydrophilic component in the support layer accounts for 2wt% to 35wt% of the dry weight of the corresponding support layer, and the cellulose hydrophilic component in the hydrophilic defect shielding layer accounts for 15wt% to 75wt% of the dry weight of the corresponding hydrophilic defect shielding layer.
3. The composite fiber supercapacitor separator according to claim 1, characterized in that, The cellulose hydrophilic component includes plant pulp and its fine components and micro / nano cellulose. The micro / nano cellulose is selected from one or more of in-situ micro / nano cellulose, microfibrillated cellulose, cellulose nanofibers, cellulose nanocrystals, and bacterial cellulose. The plant pulp and its fine components are selected from one or more of bleached hardwood pulp, bleached bamboo pulp, cellulose pulp, softwood pulp, cotton pulp, and hemp pulp. The non-conductive man-made chopped fibers are selected from one or more of polyester chopped fibers, polypropylene chopped fibers, polyethylene chopped fibers, polyamide chopped fibers, and polylactic acid chopped fibers. The microfibers are selected from one or more of the following: microfibers, split polyester fibers, polyolefin microfibers, synthetic pulp, and papermaking fine fibers. The thermal bonding fiber is selected from one or more of low melting point polyester fiber, copolyester / polyester core-sheath fiber, polyethylene / polyester core-sheath fiber and polyethylene / polypropylene core-sheath fiber; The softening point or melting point of the thermally bonded fiber is lower than that of the non-conductive man-made chopped fiber. The thermally bonded fibers are heat-pressed or heat-set to form a discontinuous dot-like bonded structure. The area coverage of the discontinuous dot-like bonded structure in the plane direction of the diaphragm is 1% to 35%, and no continuous hot melt film layer is formed inside the diaphragm.
4. The composite fiber supercapacitor separator according to claim 1, characterized in that, The average length of the non-conductive man-made chopped fibers and thermally bonded fibers is 1.0–6.0 mm, and the average linear density is 0.1–2.5 dtex; the average length of the micro-filler fibers is 0.05–1.5 mm, and the fiber width or diameter is 0.5–5.0 μm; the average length of the fine components of the plant pulp is 0.05–0.25 mm, the fiber width is 10–30 μm, and the mass ratio of the fine components is 60 wt%–95 wt%; the average length of the micro-nano cellulose is 0.5–20 μm, and the fiber diameter is 10–500 nm.
5. The composite fiber supercapacitor separator according to claim 1, characterized in that, The fiber composition of each layer, by weight, is as follows: In the support layer, there are 35 to 92 parts of non-conductive artificial short-cut fibers, 5 to 45 parts of thermal bonding fibers, 2 to 35 parts of cellulose hydrophilic components, and 5 to 25 parts of micro-fine interstitial fibers; In the hydrophilic defect shielding layer, the micro-filling fiber is 20-80 parts, the cellulose hydrophilic component is 15-75 parts, and the thermal bonding fiber or synthetic pulp is 0-35 parts; In the intermediate fluid-conducting buffer layer, there are 20 to 70 parts of non-conductive artificial short-cut fibers, 10 to 50 parts of fine interstitial fibers, 5 to 50 parts of cellulose hydrophilic components, and 0 to 30 parts of thermal bonding fibers.
6. The composite fiber supercapacitor separator according to claim 1, characterized in that, The average flow rate pore size of each of the hydrophilic defect shielding layers is independently 0.03–0.30 μm; the average flow rate pore size of each of the supporting layers is independently 0.20–2.20 μm; and the average flow rate pore size of the intermediate fluid-conducting buffer layer is 0.15–1.20 μm. Furthermore, the ratio of the average flow rate pore size of the supporting layer to the average flow rate pore size of the hydrophilic defect shielding layer is 1.8 to 12.
0.
7. The composite fiber supercapacitor separator according to claim 1, characterized in that, The diaphragm has a liquid absorption rate of 200% to 650%, a liquid retention rate of 160% to 320%, and an electrolyte wetting time of no more than 10 seconds. The interfacial peel strength of the interpenetrating fiber transition zone is not less than 0.02 N / 15 mm.
8. A method for preparing a composite fiber supercapacitor separator containing a cellulose hydrophilic gradient as described in any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Prepare slurries for the support layer, the defect shielding layer and the intermediate liquid-conducting layer respectively; wherein, each of the support layers independently comprises non-conductive artificial short-cut fibers, thermal bonding fibers and cellulose hydrophilic components; each of the hydrophilic defect shielding layers independently comprises micro-filled interstitial fibers and cellulose hydrophilic components; each of the intermediate liquid-conducting buffer layers independently comprises non-conductive artificial short-cut fibers, micro-filled interstitial fibers and cellulose hydrophilic components; (2) Segmented vacuum dehydration: K1. The first support layer is wet-formed and dehydrated on a forming wire to prepare a first wet paper web with a solid content of 7wt% to 21wt%, in the state where the first wet paper web is not dried; K2. A layer of defect shielding slurry is deposited on the surface of the first wet paper web and partially dehydrated. The deposition interval between the two slurries is controlled to be no more than 180s, and a composite wet paper web with a solid content of 12wt% to 23wt% is prepared. K3. Before the composite wet paper web is completely dry, the second support layer pulp is deposited on the composite wet paper web and partially dehydrated to obtain a wet composite membrane with a solid content of 29wt% to 36wt%. The deposition interval between the two pulp layers is controlled to not exceed 180s. This allows the adjacent pulp layers to permeate each other in a wet state, forming a fiber interpenetration transition zone between the adjacent layers. Between steps K2 and K3, the following is also included: before the composite wet paper web is completely dried, a layer of intermediate liquid-conducting buffer slurry is deposited on the composite wet paper web and partially dehydrated to obtain a wet composite paper web with a solid content of 19wt% to 25wt%. Repeat step K2 to deposit a defect shielding layer slurry on the first wet paper web, or sequentially deposit multiple layers of the alternating layer slurry and a defect shielding layer slurry, and partially dehydrate to obtain a composite wet paper web. The solid content of the composite wet paper web is greater than that of the wet composite paper web. The alternating layer includes a hydrophilic defect shielding layer and an intermediate liquid-conducting buffer layer. (3) The wet slurry after lamination is pressed, dried or heat-set in sequence to obtain the composite fiber supercapacitor membrane containing cellulose hydrophilic gradient; The thickness of the interpenetrating fiber transition region is 0.2–8.0 μm, and the composite fiber membrane has a cellulose hydrophilic gradient in the thickness direction. In step (1), the solid content of the supporting layer slurry is independently selected from 0.05wt% to 0.10wt%, the solid content of the defect shielding layer slurry is 0.015wt% to 0.050wt%, and the solid content of the intermediate liquid-conducting layer slurry is independently selected from 0.040wt% to 0.050wt%. In step (2), the time interval between the stacking deposition of two adjacent layers shall not exceed 180s; In step (3), the heat setting treatment is heat pressing or heat setting, and its process parameters are: temperature 80~170℃, linear pressure 20~300kN / m, processing time 0.1~60s. By adjusting the running direction of the forming mesh, the pulp speed ratio, the spraying direction or the lip angle of the headbox, an orientation angle of 5°~45° is formed between the orientations of the main fibers of adjacent functional layers. The cellulose lyophilic group is added to the corresponding slurry after being pulped, loosened, sieved, centrifuged, sedimented, mechanically micronized or treated with white water recovery. The thermally bonded fibers are formed into a discontinuous dot-like bonded structure after being heat-pressed or heat-set. The area coverage of the discontinuous dot-like bonded structure in the plane direction of the diaphragm is 1% to 35%, and no continuous hot melt film layer is formed inside the diaphragm. By adjusting the angle between the running direction of the forming mesh and the spraying direction of the headbox, an orientation angle of 5° to 45° is formed between the main fiber orientation of the first support layer or the second support layer and the main fiber orientation of the defect shielding layer.
9. A supercapacitor, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the composite fiber supercapacitor separator according to any one of claims 1 to 7.
10. The diaphragm according to any one of claims 1 to 7, characterized in that, It can be used in electric double-layer supercapacitors, lithium-ion capacitors, organic electrolyte supercapacitors, aqueous supercapacitors, and other electrochemical energy storage devices that require ultra-thin, high-voltage, porous insulating membranes.
